PELATIHAN LAYANAN KONSELING PASTORAL BAGI KONSELOR SEBAYA DI GEREJA PROTESTAN MALUKU KLASIS MASOHI - Noya, Andris; Taihuttu, Josias; Kiriwenno, Erlin; Aboda, Marthalus (Universitas Mataram, 2024)
Social problems in Indonesia can easily be found in various fields and places. Various problems experienced by the people require the church to be present as a government partner in providing solutions. Pastoral counseling services are one strategy that can be used to deal with various problems experienced by people in their daily lives. This training aims to improve counselors' understanding and skills regarding pastoral counseling services. The methods used in this training are lectures, discussions, simulations and role playing. This training took place at the GPM Bumei Sefluru Congregation involving participants consisting of pastors and congregation members who handle the field of pastoral counseling in the church. The results of this training can be seen in the increased understanding and skills of participants regarding pastoral counseling services.